Preparation method of biomass nitrogen-oxygen co-doped carbon material for catalyzing nitrobenzene to prepare aniline
By co-doped carbon material prepared with spirulina as the precursor, the problems of metal resource consumption and high-temperature and high-pressure reaction conditions of nitrobenzene reduction catalysts in the prior art are solved, and the preparation of aniline with high efficiency and good selectivity under mild conditions is achieved, which has environmental protection and economic advantages.
Patent Information
- Application Number
- CN202510005470.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-03-28
AI Technical Summary
In the prior art, the transition metal catalyst for the reduction of nitrobenzene to prepare aniline consumes metal resources, poses environmental burdens and safety hazards, and requires high temperature and high pressure reaction conditions.
The biomass nitrogen-oxygen co-doped carbon material prepared with spirulina as the precursor was used as a catalyst to prepare carbon-based materials without additional doping by carbonization treatment in tube furnaces, and used to catalyze the selective hydrogenation of nitrobenzene to prepare aniline.
It realizes efficient reduction of nitrobenzene under mild conditions, has high selectivity and stability, avoids the danger of high temperature and high pressure, and the catalyst can be reused, environmentally friendly and economical.
Smart Images

Figure CN119702044A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of new materials and catalytic technology, and involves national key development industries such as biomass recycling, agricultural product processing, energy conservation and environmental protection, and fine chemicals. More specifically, it is a method for preparing carbon materials using spirulina as a precursor to catalyze the selective hydrogenation of nitrobenzene to produce aniline. Background Art
[0002] Nitrobenzene is a highly toxic compound, and its reduced product aniline is widely used in the production of rubber, dyes, agricultural chemicals and pharmaceuticals. At present, transition metals such as Fe, Ni, and Pd are the most commonly used active centers in the reduction of nitrobenzene. These catalysts not only consume metal resources but also cause environmental burdens in subsequent treatment. The reduction process also often requires high temperature and high pressure reaction conditions, which are unsafe. Therefore, safe, environmentally friendly and reusable non-metallic catalysts for the reduction of nitrobenzene to aniline are urgently needed to be developed.
[0003] Biomass waste has always been considered a low-value material with low utilization rate. Agricultural waste such as soybean stalks are usually burned or naturally converted into organic fertilizer. However, such treatment methods may cause further environmental problems. For example, the burning of waste will release a large amount of pollutants such as carbon monoxide, nitrous oxide, nitrogen dioxide and smoke particles into the atmosphere, causing air pollution. Biomass material is a renewable natural resource with a unique structure and rich heteroatoms (nitrogen, oxygen, phosphorus, sulfur, etc.), which makes it have good prospects in the application of preparing catalysts. Many different types of biomass materials, such as rice husks, leather, tea branches and peony shells, have been used as precursors for the production of porous carbon or heteroatom-doped carbon with good catalytic performance.
[0004] Patent ZL2019109625487 discloses a method for preparing a nickel-loaded catalyst based on lotus shells, wherein a mixture of lotus shell powder loaded with nickel acetate, zinc powder, and zinc chloride-potassium chloride is carbonized at 700-800 °C for 2-6 h under an inert gas atmosphere to finally obtain a nickel-loaded catalyst based on lotus shells, which is used to catalyze the hydrogenation of p-nitrophenol to prepare p-aminophenol. Patent ZL2021114639646 discloses a method for preparing an Fe-based catalyst using biomass tea leaves as raw materials, and is applied to the catalytic hydrogenation reaction of p-chloronitrobenzene. Patent ZL2023101172146 discloses a preparation method and application of a chitosan-based Pt-Ni bimetallic catalyst. Chitosan nanofiber microspheres are prepared from shrimp shell and crab shell powder by a microemulsion method. Metal precursor salts of platinum compounds and nickel compounds are dissolved in deionized water. The two are mixed and stirred for impregnation and adsorption to prepare a catalyst. Sodium borohydride is used as a reducing agent, and the nitro group can be hydrogenated to an amine group under mild reaction conditions, with a selectivity of up to 99%. In this system, the reaction can be completed at normal pressure, avoiding the dangerous factors caused by high pressure in the reaction, but the sodium borohydride reducing agent is toxic and irritating and has a high chemical reactivity, which is not conducive to industrial production safety. Although the biomass carbon materials prepared in the above patents all have good catalytic properties, they all need to be additionally doped or loaded with other substances, which makes the production process more cumbersome and increases the production cycle and cost. Therefore, it is more valuable to prepare biomass-based nitroaromatic reduction catalytic materials that can be reused under mild experimental conditions without additional doping.
[0005] Among various biomass materials, algae have attracted much attention due to their fast growth rate, high photosynthetic efficiency, and minimal competition with food resources. In addition, algae can be grown in various environments, including wastewater and salt water, thus avoiding the use of precious freshwater resources. Among them, Spirulina is a widely used microbial resource. Compared with other algae, Spirulina itself has a high nitrogen content and can be prepared into nitrogen-oxygen co-doped carbon materials after high-temperature carbonization, which has potential application value. Exploring the preparation of biomass carbon material catalysts with Spirulina as a precursor is not only of economic value but also of environmental value, and has great application prospects. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing a carbon-based material for catalyzing the hydrogenation of nitrobenzene using biomass as a precursor, which is green, economical, efficient, stable and reusable. The material has a wide range of sources and low cost; it does not require additional doping with other substances; it can efficiently reduce nitrobenzene under mild conditions; and it has high selectivity for aniline.
[0007] In order to achieve the above object, the present invention adopts the following technical solution: A method for preparing a biomass nitrogen-oxygen co-doped carbon material for catalyzing nitrobenzene to produce aniline, characterized in that it comprises the following steps: The ultrafine spirulina powder was placed in a tubular furnace, and 30 mL / min of nitrogen was used as a protective gas. The temperature was raised to the target temperature at a rate of 5 ℃ / min for a certain period of pre-carbonization, and naturally cooled to room temperature to obtain a pre-carbonized sample; the pre-carbonized sample was added with deionized water and magnetically stirred for 12 h, and the obtained suspension was poured into a reactor for hydrothermal treatment, cooled, filtered, washed, and vacuum dried to obtain a hydrothermal sample; the hydrothermal sample and KOH solution were mixed evenly in proportion, dried at 80 ℃, ground, placed in a tubular furnace, and carbonized with 30 mL / min of nitrogen as a protective gas. The carbonized product was thoroughly washed with 1 mol / L hydrochloric acid solution and deionized water to neutrality, and vacuum dried to obtain a black powder nitrogen-oxygen co-doped carbon material; The method for preparing aniline from nitrobenzene by catalyzing the obtained nitrogen and oxygen co-doped carbon material is as follows: (1) The nitrogen-oxygen co-doped carbon material is uniformly dispersed in a solvent, and then the reactant nitrobenzene and the reducing agent hydrazine hydrate are added, heated and magnetically stirred, and samples are taken after a period of reaction, and detected by gas chromatography to calculate the conversion rate of nitrobenzene and the selectivity and yield of aniline; (2) The used nitrogen-oxygen co-doped carbon material can be recycled after repeated washing and vacuum drying; (3) After the first experiment was interrupted and sampling was performed, the catalyst was filtered out while hot and washed with anhydrous ethanol for several times. The washing liquid and the filtrate were collected and the reaction was continued under the original experimental conditions. The stability of the carbon-based material was tested by gas chromatography.
[0008] Preferably, in the above-mentioned method for preparing biomass nitrogen and oxygen co-doped carbon material for catalyzing nitrobenzene to produce aniline, it is characterized in that the pre-carbonization target temperature is 300-500°C and the time is 2-4 h.
[0009] The beneficial effect of the above technical solution is to remove impurities such as bio-oil in biomass and leave biomass carbon.
[0010] Preferably, in the above-mentioned method for preparing a biomass nitrogen-oxygen co-doped carbon material for catalyzing nitrobenzene to produce aniline, it is characterized in that the hydrothermal treatment temperature is 110-180° C. and the time is 2-12 h.
[0011] The beneficial results of the above technical solution are: stabilizing the structure of the carbon material, helping to retain the impurity elements such as N and O in the carbon material, and improving the catalytic performance.
[0012] Preferably, in the above-mentioned method for preparing biomass nitrogen and oxygen co-doped carbon material for catalyzing nitrobenzene to produce aniline, it is characterized in that the ratio of the hydrothermal sample to the KOH solution is 1 g: (0.9~4.5) mol / L.
[0013] The beneficial result of the above technical solution is that KOH reacts with the carbon material to promote the growth of carbon pores and increase the specific surface area.
[0014] Preferably, in the above-mentioned method for preparing biomass nitrogen-oxygen co-doped carbon material for catalyzing nitrobenzene to produce aniline, it is characterized in that the carbonization treatment is divided into two stages; in the first stage, the temperature is increased from room temperature at 10°C / min to 400°C, and carbonized for 60 min; in the second stage, the temperature is increased to the carbonization temperature (600°C, 700°C, 800°C) at 5°C / min, and carbonized for 120 min.
[0015] The beneficial results of the above technical solution are as follows: the carbonization temperature affects the graphitization degree of the material, thereby affecting the catalytic performance of the material in hydrogenation of nitrobenzene; at the same time, the nitrogen species in the material will also affect the catalytic performance.
[0016] Preferably, in the above-mentioned method for preparing a biomass nitrogen-oxygen co-doped carbon material for catalyzing nitrobenzene to produce aniline, it is characterized in that the solvent in step (1) is any one of acetonitrile, ethanol and cyclohexane.
[0017] The beneficial effect of the above technical solution is that solvents with stronger polarity will form competitive adsorption with nitrobenzene on the catalyst surface, thereby reducing the catalytic efficiency and the reaction conversion rate, while solvents with weaker polarity will increase the reaction conversion rate.
[0018] Preferably, in the above-mentioned method for preparing a biomass nitrogen-oxygen co-doped carbon material for catalyzing nitrobenzene to produce aniline, it is characterized in that in step (1), the addition ratio of the nitrogen-oxygen co-doped carbon material to nitrobenzene and hydrazine hydrate is (5~15) mg:0.5 mmol:(2~5 mmol).
[0019] The beneficial effect of the above technical solution is that the conversion rate of nitrobenzene can be increased by appropriately increasing the amount of catalyst used. Hydrazine hydrate is the hydrogen source for the reaction. Compared with hydrogen, hydrazine hydrate is green, environmentally friendly, has a low risk of explosion, and is easy to transport and store.
[0020] Preferably, in the above-mentioned method for preparing a biomass nitrogen-oxygen co-doped carbon material for catalyzing nitrobenzene to produce aniline, it is characterized in that the reaction temperature in step (1) is 60-80° C. and the reaction time is 0.05-0.75 h.
[0021] It can be seen from the above technical solution that, compared with the prior art, the present invention discloses a method for preparing spirulina ultrafine powder into a carbon-based material by carbonization in a tubular furnace and its catalytic application in the hydrogenation reaction of nitrobenzene, which has the following advantages: (1) In terms of catalyst preparation, the raw material Spirulina is a renewable biomass resource that is rich in nitrogen and does not require additional doping with other substances. It is cheap and easy to obtain, the preparation process is simple, the preparation conditions are easy to control, the synthesis route is simple, and it is suitable for industrial production.
[0022] (2) In terms of catalytic nitrobenzene hydrogenation reaction, the catalytic system requires mild conditions, avoiding the danger of high temperature and high pressure. Compared with other reducing agents, hydrazine hydrate has a lower risk of explosion, is easy to transport and store, and has low corrosiveness to experimental equipment. The catalyst has good catalytic activity, catalytic efficiency and stability, and can be reused many times without reducing the catalytic effect. It has application potential in the fields of industrial catalysts and fine chemical synthesis.
[0023] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0025] Attached Figure 1 This is a scanning electron microscope image of SPC-800; Attached Figure 2 N2 adsorption-desorption curve (a) and pore distribution curve (b) of SPC-800; Attached Figure 3 This is the X-ray photoelectron spectrum of SPC-800; Attached Figure 4 is the Raman spectrum of SPC-800; Attached Figure 5 It is a line graph of the hydrogenation reaction of nitrobenzene catalyzed by SPC-800; Attached Figure 6 This is a bar chart of the cyclic experiment of nitrobenzene hydrogenation reaction catalyzed by SPC-800. Specific implementation methods
[0026] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] The embodiment of the present invention discloses a method for preparing a biomass nitrogen-oxygen co-doped carbon material for catalyzing nitrobenzene to produce aniline. The steps for preparing the material are as follows: (1) Preparation of pre-carbonized samples: Spirulina ultrafine powder was placed in a tubular furnace, and nitrogen was used as a protective gas at a rate of 30 mL / min. The temperature was raised to 350 ℃, 400 ℃, and 450 ºC at a rate of 5 ℃ / min. The pre-carbonized samples were obtained after being naturally cooled to room temperature for 2 h. (2) Preparation of hydrothermal samples: 1.0 g of pre-carbonized sample was added with 30 mL of deionized water and magnetically stirred for 12 h. The resulting suspension was poured into a reactor and hydrothermally treated for 12 h at 120 °C, 150 °C, and 180 °C. The sample was cooled, filtered, washed, and vacuum dried at 80 °C for 12 h to obtain a hydrothermal sample. (3) Mixing the hydrothermal sample with KOH solution: 1.0 g of the hydrothermal sample and 20 mL of KOH solution (with concentrations of 0.9 mol / L, 2.7 mol / L, and 4.5 mol / L, respectively) were mixed evenly, dried at 80 °C, and then ground; (4) Preparation of SPC-X: The above samples were placed in a tubular furnace and carbonized with 30 mL / min nitrogen as the protective gas at 600 ºC, 700 ºC and 800 ℃ for 2 h. The carbonized products were washed thoroughly with 1 mol / L hydrochloric acid solution and deionized water until neutral, and then dried in vacuo to obtain black powder nitrogen-oxygen co-doped carbon materials, which were named SPP-350, SPP-400, SPP-450, SPH-120, SPH-150, SPH-180, SPK-1:0.9, SPK-1:2.7, SPK-1:4.5, SPC-600, SPC-700 and SPC-800.
[0028] Based on the preparation of the above-mentioned SPC-X catalyst provided by the present invention, the applicant has studied the catalytic performance of the SPC-X material in the hydrogenation reaction of nitrobenzene. The steps of the catalytic reaction are as follows: Catalyst SPC-X, 4 mL of organic solvent, 0.5 mmol of nitrobenzene, and 2-5 mmol of hydrazine hydrate were added to a round-bottom flask equipped with a reflux condenser and magnetic stirring, and heated with magnetic stirring. After a certain reaction time, samples were taken, filtered through a filter membrane, and the conversion rate of nitrobenzene and the yield of aniline were detected by gas chromatography.
[0029] The gas phase detection conditions were as follows: vaporization chamber 240 °C, detector 280 °C, initial column temperature 80 °C, heating to 160 °C at 10 °C / min, holding for 1 min, then heating to 240 °C at 20 °C / min, holding for 10 min.
[0030] Examples 1-12 in Table 1 demonstrate the catalytic effects of catalysts prepared under different conditions on the hydrogenation of nitrobenzene; the reaction conditions of Examples 1-12 are 15 mg of catalyst, a molar ratio of nitrobenzene to hydrazine hydrate of 1:10, a reaction temperature of 80 °C, and a solvent of 4 mL of ethanol; the reaction time is 0.75 h; the selectivity of all catalysts for aniline is greater than 99.9%.
[0031] Table 1 Catalytic application effects of different catalysts in nitrobenzene hydrogenation reaction Example catalyst Pre-carbonization temperature (℃) Water temperature (℃) Ratio of hydrothermal sample to KOH solution (g:mol / L) Carbonization temperature (℃) Nitrobenzene conversion rate (%) 1 SPP-350 350 150 1:4.5 800 73 2 SPP-400 400 150 1:4.5 800 100 3 SPP-450 450 150 1:4.5 800 47 4 SPH-120 400 120 1:4.5 800 87 5 SPH-150 400 150 1:4.5 800 100 6 SPH-180 400 180 1:4.5 800 77 7 SPK-1:0.9 400 150 1:0.9 800 40 8 SPK-1:2.7 400 150 1:2.7 800 62 9 SPK-1:4.5 400 150 1:4.5 800 100 10 SPC-600 400 150 1:4.5 600 83 11 SPC-700 400 150 1:4.5 700 88 12 SPC-800 400 150 1:4.5 800 100 In Table 1, the pre-carbonization temperatures of Examples 1, 2, and 3 are 350, 400, and 450 °C, respectively; the hydrothermal temperatures of Examples 4, 5, and 6 are 120, 150, and 180 °C, respectively; the ratios of the hydrothermal sample to KOH in Examples 7, 8, and 9 are 1:0.9, 1:2.7, and 1:4.5, respectively; and the carbonization temperatures of Examples 10, 11, and 12 are 600, 700, and 800 °C, respectively.
[0032] Specifically, it can be seen from Examples 1, 2, and 3 that the pre-carbonization temperature in the catalyst synthesis process is different, and other preparation conditions and catalytic reaction conditions are the same. From the experimental data, it can be seen that SPP-400 with a pre-carbonization temperature of 400°C has a better catalytic effect in the catalytic nitrobenzene hydrogenation reaction.
[0033] In Examples 4, 5, and 6, except for the different hydrothermal temperatures, other preparation conditions and catalytic reaction conditions are the same. It can be seen from the experimental data that with the increase of the hydrothermal temperature, the conversion rate of the catalytic nitrobenzene hydrogenation reaction increases, but when the hydrothermal temperature rises to 180°C, the conversion rate decreases. SPH-150 with a hydrothermal temperature of 150°C has a better catalytic effect in the catalytic nitrobenzene hydrogenation reaction.
[0034] In Examples 7, 8, and 9, except for the different mixing ratios of the hydrothermal sample and the KOH solution, other preparation conditions and catalytic reaction conditions are the same. Considering the catalytic effect and the yield of the catalyst, the mixing ratio of the hydrothermal sample and the KOH solution is selected to be 1 g:4.5 mol / L.
[0035] In Examples 10, 11, and 12, except for the carbonization temperature, the other preparation conditions and catalytic reaction conditions are the same. It can be seen from the experimental data that SPC-800 has a better catalytic effect in the catalytic nitrobenzene hydrogenation reaction. The carbonization temperature will affect factors such as the graphitization degree, nitrogen species distribution, and specific surface area of SPC-800, thereby affecting the catalytic performance of the material.
[0036] Examples 13-23 in Table 2 demonstrate the catalytic effect of SPC-800 on nitrobenzene hydrogenation under different reaction conditions.
[0037] Table 2 Catalytic application effect of SPC-800 in nitrobenzene hydrogenation reaction Example catalyst Catalyst dosage mg Hydrazine hydrate mmol Temperature (℃) Solvents Time (h) Nitrobenzene conversion rate (%) 13 none 0 5 80 Cyclohexane 0.15 0 14 SPC-800 15 5 80 Ethanol 0.15 13 15 SPC-800 15 4 80 Ethanol 0.15 18 16 SPC-800 15 3 80 Ethanol 0.15 20 17 SPC-800 15 2 80 Ethanol 0.15 27 18 SPC-800 15 5 80 Acetonitrile 0.15 13 19 SPC-800 15 5 80 Cyclohexane 0.15 100 20 SPC-800 15 5 70 Cyclohexane 0.15 91 21 SPC-800 15 5 60 Cyclohexane 0.15 61 22 SPC-800 10 5 80 Cyclohexane 0.15 87 23 SPC-800 5 5 80 Cyclohexane 0.15 39 In Table 2, Example 13 is a blank experiment; the amount of hydrazine hydrate added in Examples 14, 15, 16, and 17 is 5, 4, 3, and 2 mmol, respectively; the solvents added in the reactions of Examples 14, 18, and 19 are ethanol, acetonitrile, and cyclohexane, respectively; the temperatures for catalytic nitrobenzene hydrogenation reactions in Examples 19, 20, and 21 are 80, 70, and 60° C., respectively; the amount of SPC-800 used in Examples 19, 22, and 23 is 15, 10, and 5 mg, respectively; Specifically, it can be seen from the experimental data of Examples 13 and 19 that: under the same experimental conditions, the hydrogenation of nitrobenzene did not react in the blank experiment, and the addition of the SPC-800 material had an obvious catalytic effect on the hydrogenation reaction of nitrobenzene.
[0038] In Examples 14, 15, 16, and 17, except for the different amounts of the reducing agent hydrazine hydrate, the other catalytic reaction conditions are the same. It can be seen from the experimental data that after 0.15 h of reaction, when the molar ratio of nitrobenzene to hydrazine hydrate is 1:10, the conversion rate of nitrobenzene is relatively high.
[0039] In Examples 14, 18 and 19, except for the different solvents added, other catalytic reaction conditions are the same. Experiments have found that solvents with low polarity promote the conversion of nitrobenzene, and the conversion rate of nitrobenzene is higher in the reaction using cyclohexane as the solvent.
[0040] In Examples 19, 20, and 21, except for the different reaction temperatures in the catalytic reaction, other catalytic reaction conditions are the same. It can be seen from the experimental data that the increase in reaction temperature is conducive to the conversion of nitrobenzene. In Example 19, the reaction temperature is 80°C, the conversion rate of nitrobenzene is 100%, and the selectivity of aniline is 100%.
[0041] In Examples 19, 22, and 23, except for the different amounts of the catalyst SPC-800, the other catalytic reaction conditions are the same. From the experimental data, it can be seen that in Example 19, the amount of catalyst SPC-800 added is the largest, the nitrobenzene conversion rate is the highest, and the catalytic effect is good. However, considering the cost of raw materials, the preferred amount of SPC-800 is 10 mg.
[0042] In addition, SPC-800 was tested by scanning electron microscope. Figure 1 This is an SPC-800 scanning electron microscope image. The sample is composed of irregular nanoparticles, and there are cracks and holes on the sample surface.
[0043] Attached Figure 2 a is the N2 adsorption-desorption curve of SPC-800. It can be observed that SPC-800 conforms to the characteristics of type I isotherm, and the specific surface area is 1425 m 2 ·g -1 , the pore volume is 0.81 cm 3 ·g -1 Attached Figure 2 b is the pore size distribution curve of SPC-800. The most probable pore size is around 0.8 nm, indicating that most of the pores in the material are in micropore size.
[0044] Attached Figure 3 This is the X-ray photoelectron spectroscopy (XPS) of the SPC-800 catalyst. The sample contains C, O, and N elements (pyridinic N, pyrrolic N, graphitic N, and oxidized N).
[0045] Attached Figure 4 This is the Raman spectrum of SPC-800. As shown in the figure, the 1350 cm -1 The D band at 1580 cm represents the disorder or defect structure of carbon atoms, while the -1 The G band at sp 2 Hybridized graphite carbon. The ID / IG ratio of SPC-800 is 0.82, which indicates that there are defect sites in SPC-800. Related reports show that the degree of defect will affect the effect of catalytic reduction reaction.
[0046] Attached Figure 5It is a line graph showing the change of aniline yield with reaction time when catalyzing nitrobenzene hydrogenation reaction. Curve a is a line graph showing the change of aniline yield with reaction time when 10 mg SPC-800 catalyst is used in 4 mL cyclohexane as solvent, 5 mmol hydrazine hydrate as reducing agent, and 0.5 mmol nitrobenzene is hydrogenated at 80 °C. Samples were taken and analyzed at 0.05 h, 0.1 h, 0.15 h, 0.2 h, and 0.25 h of reaction. Curve b is a line graph showing the change of aniline yield with reaction time after the reaction was interrupted at 0.15 h of reaction. Figure 5 The a and b curves indicate that SPC-800 has good stability in this reaction system.
[0047] Attached Figure 6 This is a bar chart of the SPC-800 catalytic nitrobenzene hydrogenation reaction cycle experiment. Figure 6 It can be seen that after the catalyst has been used five times, the selectivity of aniline is 100% and the conversion rate of nitrobenzene is 94%, indicating that SPC-800 can be recycled at least five times and has good reusability.
[0048] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the scheme disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.
[0049] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a biomass nitrogen-oxygen co-doped carbon material for catalyzing nitrobenzene to produce aniline, characterized in that: The following steps are involved: The ultrafine spirulina powder was placed in a tubular furnace, and 30 mL / min of nitrogen was used as a protective gas. The temperature was raised to the target temperature at a rate of 5 ℃ / min for a certain period of pre-carbonization, and naturally cooled to room temperature to obtain a pre-carbonized sample; the pre-carbonized sample was added with deionized water and magnetically stirred for 12 h, and the obtained suspension was poured into a reactor for hydrothermal treatment, cooled, filtered, washed, and vacuum dried to obtain a hydrothermal sample; the hydrothermal sample and KOH solution were mixed evenly in proportion, dried at 80 ℃, ground, placed in a tubular furnace, and carbonized with 30 mL / min of nitrogen as a protective gas. The carbonized product was thoroughly washed with 1 mol / L hydrochloric acid solution and deionized water to neutrality, and vacuum dried to obtain a black powder nitrogen-oxygen co-doped carbon material; The method for preparing aniline from nitrobenzene by catalyzing the obtained nitrogen and oxygen co-doped carbon material is as follows: (1) The nitrogen-oxygen co-doped carbon material is uniformly dispersed in a solvent, and then the reactant nitrobenzene and the reducing agent hydrazine hydrate are added, heated and magnetically stirred, and samples are taken after a period of reaction, and detected by gas chromatography to calculate the conversion rate of nitrobenzene and the selectivity and yield of aniline; (2) The used nitrogen-oxygen co-doped carbon material can be recycled after repeated washing and vacuum drying; (3) After the first experiment was interrupted and sampling was performed, the catalyst was filtered out while hot and washed with anhydrous ethanol for several times. The washing liquid and the filtrate were collected and the reaction was continued under the original experimental conditions. The stability of the carbon-based material was tested by gas chromatography.
2. The method for preparing a biomass nitrogen-oxygen co-doped carbon material for catalyzing nitrobenzene to produce aniline according to claim 1, characterized in that: The pre-carbonization target temperature is 300~500°C and the time is 2~4 hours.
3. The method for preparing a biomass nitrogen-oxygen co-doped carbon material for catalyzing nitrobenzene to produce aniline according to claim 1, characterized in that: The hydrothermal treatment temperature is 110-180°C and the time is 2-12 h.
4. The method for preparing a biomass nitrogen-oxygen co-doped carbon material for catalyzing nitrobenzene to produce aniline according to claim 1, characterized in that: The ratio of the hydrothermal sample to the KOH solution is 1 g: (0.9~4.5) mol / L.
5. The method for preparing a biomass nitrogen-oxygen co-doped carbon material for catalyzing nitrobenzene to produce aniline according to claim 1, characterized in that: The carbonization treatment is divided into two stages; in the first stage, the temperature is increased from room temperature to 400°C at 10°C / min and carbonized for 60 min; in the second stage, the temperature is increased to the carbonization temperature (600°C, 700°C, 800°C) at 5°C / min and carbonized for 120 min.
6. The method for preparing a biomass nitrogen-oxygen co-doped carbon material for catalyzing nitrobenzene to produce aniline according to claim 1, characterized in that: The solvent in step (1) is any one of acetonitrile, ethanol and cyclohexane.
7. The method for preparing a biomass nitrogen-oxygen co-doped carbon material for catalyzing nitrobenzene to produce aniline according to claim 1, characterized in that: In step (1), the addition ratio of nitrogen and oxygen co-doped carbon material to nitrobenzene and hydrazine hydrate is (5-15) mg:0.5 mmol:(2-5 mmol).
8. The method for preparing a biomass nitrogen-oxygen co-doped carbon material for catalyzing nitrobenzene to produce aniline according to claim 1, characterized in that: In step (1), the reaction temperature is 60-80°C and the reaction time is 0.05-0.75 h.